A STUDY ON IDENTIFICATION OF PRODUCT VALUE BASED ON PATENT ANALYSIS: THE CASE OF THE PROJECTORS - Masuda, Koji (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2022)
Companies are required to understand the external environment, develop growth strategies, and implement them. One aspect of the external environment is the market itself. To understand customer needs, we use patent information as the approach from the product, rather than the approach of listening to the voice of the customer, based on the three levels of product. We proposed a method to show the value of a product based on the concept of commonality and uniqueness by comparing multiple samples. In the case of projectors, Japanese patents were analyzed. We conclude that the common content represents the core benefits of the product, and that the characteristic content represents the product attributes